Isolation and Culture of Primary Pericytes from Mouse - Tamara McErlain; Cristina Branco; Meera Murgai (Bio-Protocol)
Pericytes are essential for tissue homeostasis, functioning to regulate capillary blood flow. Dysfunctional pericytes are implicated in various pathologies, including cancer progression. Despite their important function in both health and disease, pericytes remain understudied due to a lack of robust model systems that accurately reflect their in vivo biology. Here, we present a comprehensive protocol for isolating and culturing primary pericytes from murine lung, brain, bone, and liver tissues, based on NG2 expression using an antibody-conjugated magnetic bead approach. Our protocol emphasizes the importance of physiological oxygen tension during ex vivo culture (10% O2 for lung pericytes and 5% O2 for brain, bone, and liver pericytes). These conditions stabilize the expression of characteristic pericyte markers at both the transcriptional and protein levels. Importantly, we optimized growth conditions to limit the expression of the plasticity factor Klf4 in order to prevent spontaneous phenotypic switching in vitro. This protocol provides a reliable and reproducible method for obtaining pericytes suitable for high-throughput analyses in order to explore pericyte biology in both physiological and pathological contexts.